Durable Clinical Response to Entrectinib in NTRK1-Rearranged Non-Small Cell Lung Cancer. Issue 12 (December 2015) - Farago, Anna F.; Le, Long P.; Zheng, Zongli; Muzikansky, Alona; Drilon, Alexander; Patel, Manish; Bauer, Todd M.; Liu, Stephen V.; Ou, Sai-Hong I.; Jackman, David; Costa, Daniel B.; Multani, Pratik S.; et al.
Abstract : Introduction: Chromosomal rearrangements involving neurotrophic tyrosine kinase 1 ( NTRK1 ) occur in a subset of non-small cell lung cancers (NSCLCs) and other solid tumor malignancies, leading to expression of an oncogenic TrkA fusion protein. Entrectinib (RXDX-101) is an orally available tyrosine kinase inhibitor, including TrkA. We sought to determine the frequency of NTRK1 rearrangements in NSCLC and to assess the clinical activity of entrectinib. Methods: We screened 1378 cases of NSCLC using anchored multiplex polymerase chain reaction (AMP). A patient with an NTRK1 gene rearrangement was enrolled onto a Phase 1 dose escalation study of entrectinib in adult patients with locally advanced or metastatic tumors (NCT02097810). We assessed safety and response to treatment. Results: We identified NTRK1 gene rearrangements at a frequency of 0.1% in this cohort. A patient with stage IV lung adenocrcinoma with an SQSTM1-NTRK1 fusion transcript expression was treated with entrectinib. Entrectinib was well tolerated, with no grade 3–4 adverse events. Within three weeks of starting on treatment, the patient reported resolution of prior dyspnea and pain. Restaging CT scans demonstrated a RECIST partial response (PR) and complete resolution of all brain metastases. This patient has continued on treatment for over 6 months with an ongoing PR. Conclusions: Entrectinib demonstrated significant anti-tumor activity in a patient with NSCLC harboring an SQSTM1-NTRK1 gene rearrangement, indicating that entrectinib may be an effective therapy for tumors with NTRK gene rearrangements, including those with central nervous system metastases.